2010
DOI: 10.1093/carcin/bgq066
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-34a suppresses invasion through downregulation of Notch1 and Jagged1 in cervical carcinoma and choriocarcinoma cells

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that regulate the expression of other genes by transcriptional inhibition or translational repression. miR-34a is a known tumor suppressor gene and inhibits abnormal cell growth. However, its role in other tumorigenic processes is not fully known. This study aimed to investigate the action of miR-34a on cell invasion. We found that miR-34a is expressed at various levels in cervical cancer (HeLa, SiHa, C4I, C33a and CaSki) and trophoblast (BeWo and JAR) cell lines. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
172
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(181 citation statements)
references
References 55 publications
8
172
1
Order By: Relevance
“…In addition, HeLa cells that stably overexpressed miR-214 downregulated the expression of MEK3 and JNK1 at both the mRNA and protein levels by targeting the 3'UTRs of these genes (22). Finally, it has been reported that miR-34a inhibits invasiveness through regulation of the Notch pathway and its downstream matrix degrading enzyme in cervical cancer (23). In our study, we found that miR-143 was underexpressed in 86.7% of the cancerous cervical tissues compared with their non-tumor counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HeLa cells that stably overexpressed miR-214 downregulated the expression of MEK3 and JNK1 at both the mRNA and protein levels by targeting the 3'UTRs of these genes (22). Finally, it has been reported that miR-34a inhibits invasiveness through regulation of the Notch pathway and its downstream matrix degrading enzyme in cervical cancer (23). In our study, we found that miR-143 was underexpressed in 86.7% of the cancerous cervical tissues compared with their non-tumor counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed the MMP mRNA transcripts harbor specific sequences in their 5' or 3' untranslated regions (UTRs) which are potential targets of regulatory proteins involved in mRNA stability (39). On the other hand, HDI treatment may activate miRNA expression and modulate tumor cell invasiveness (42)(43)(44)(45). For instance, miR22 was shown to be upregulated by TSA treatment but not by 5-azadC (42).…”
Section: Discussionmentioning
confidence: 99%
“…miR-124 and miR-34, well defined tumor suppressors, are subject to epigenetic silencing by aberrant DNA hypermethylation affecting cell cycle pathways in tumors 54,57,58 ; while down-regulation of miR-34 affects the Notch pathway involved in cell invasion and apoptosis. 59 Furthermore, DNA methylation profiles in miRNA promoter regions can be useful as a diagnostic and prognostic marker. For example, miR-23b, a miRNA with tumor suppressor activity in prostate cancer, is down-regulated through DNA hypermethylation of its promoter region and its expression level is correlated with overall survival and recurrence-free survival.…”
Section: Epigenetic Alterations At Mirna Locimentioning
confidence: 99%